Characterization of Indonesian Bamboo Charcoal for Enhanced Adsorption Capabilities - Suryandari, Ervin Tri; Abdul Keyon, Aemi Syazwani (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
Bamboo charcoal from four types of Indonesian bamboo species had been successfully prepared and characterized. The yield was 19.67%; 30.86%; 33,16% and 27,34 respectively for Apus bamboo, Javanese bamboo, Ori bamboo and Yellow bamboo. The activation of bamboo charcoal was carried out chemically using KOH and H3PO4. Activated bamboo charcoal was characterized for the content of water, volatile substance, total ash, and carbon, as well as iodine absorption capacity based on the technical standard of activated carbon SNI 06-3730-1995. The activated bamboo charcoal was also characterized using Fourier Transform Infrared (FTIR) to determine the functional groups, SEM to determine morphology and nitrogen adsorption desorption to determine the surface area. The activation process was able to reduce water, ash, volatile substance content; thereby increasing carbon content which has the potential to be used for adsorption, and this is evidenced by the increase in the value of iodine absorption. From the FTIR data activated bamboo charcoal shows the presence of a C=O at 1500-1600 cm-1, O-H at 3400-3500 cm-1 and CO at 1300-1400 cm-1 which has the potential to contribute the active site for adsorptionprocess. Based on SEM data the morphology of activated bamboo charcoal was porous. Enhance quantity of pores would increase the surface area and the adsorption ability. From the results of the surface area data, it was found that the 4 types of activated bamboo charcoal produced a higher surface area, and activation using KOH was more effective than H3PO4in increasing the surface area of activated bamboo charcoal.